Allelopathic effect of invasive species air potato (Dioscorea bulbifera) on seeds germination of Polyalthia littoralis: ALELOPATI TUMBUHAN INVASIF Dioscorea bulbifera L. TERHADAP PERKECAMBAHAN BIJI Polyalthia littoralis (Blume) Boerl - ADE AYU OKSARI; DEVY SUSANTY; IRVAN FADLI WANDA (Nusantara Bioscience, 2019)
Abstract. Oksari AA, Susanty D, Wanda IF. 2019. Allelopathic effect of invasive species air potato (Dioscorea bulbifera) on seeds germination of Polyalthia littoralis. Nusantara Bioscience 11: 63-70. Dioscorea bulbifera L. (Dioscoreaceae) is included in the Global Weed Compendium and one of the invasive plants that cause environmental problems in many parts of the world. This study aims to determine the effect of allelopathy from various concentrations of leaf and tuber extract from D. bulbifera on seed germination of Polyalthia littoralis (Blume) Boerl. The method used was a Completely Randomized Design (CRD) with seven treatments and three replications. The treatment given was the concentration of D. bulbifera extract 10%, 20%, 40%, 60%, 80%, 100% and aquadest solvent control. The results of phytochemical screening analysis showed that the extract of leaves and tuber of D. bulbifera did not contain alkaloids, but specifically on leaves extract contained tannins. Both extracts contained steroids, flavonoids, and saponins. Based on the results of the study, total phenolic obtained in the leaf extract as much as 28.81 ± 2.51 mg TAE/g extract, while the tuber extract had a total phenolic of 6.74 ± 1.19 mg TAE/g. The results showed that allelopathic substances of D. bulbifera affected the germination of P. littoralis seeds. Based on DMRT test at 5% level, it was known that allelopathy concentration of D. bulbifera significantly affected the germination rate at concentrations of 20%, 60%, 80%, and 100% and significantly affected the coefficient of velocity of germination at a concentration of 20%. But, concentration allelopathy of D. bulbifera had no significant effect on the coefficient of uniformity of germination. The concentration that reduced the lowest seed viability was at a concentration of 80% with an average germination power of 56.67 ± 7.45%.